2021
DOI: 10.1371/journal.pbio.3001434
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium NOT1-G paralogue is an essential regulator of sexual stage maturation and parasite transmission

Abstract: Productive transmission of malaria parasites hinges upon the execution of key transcriptional and posttranscriptional regulatory events. While much is now known about how specific transcription factors activate or repress sexual commitment programs, far less is known about the production of a preferred mRNA homeostasis following commitment and through the host-to-vector transmission event. Here, we show that in Plasmodium parasites, the NOT1 scaffold protein of the CAF1/CCR4/Not complex is duplicated, and one … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…mRNA targets are bound by Pf Puf2, the disruption of which results in translation and the increased production of the associated protein ( Miao et al., 2013 ). Those transcripts not stabilized are regulated by the CAF1/CCR4/NOT complex causing mRNA decay and thereby translational repression ( Figure 3 ) ( Hart et al., 2019 ; Hart et al., 2021 ).…”
Section: Maturation Of Gametocytes To Transmissible Formsmentioning
confidence: 99%
“…mRNA targets are bound by Pf Puf2, the disruption of which results in translation and the increased production of the associated protein ( Miao et al., 2013 ). Those transcripts not stabilized are regulated by the CAF1/CCR4/NOT complex causing mRNA decay and thereby translational repression ( Figure 3 ) ( Hart et al., 2019 ; Hart et al., 2021 ).…”
Section: Maturation Of Gametocytes To Transmissible Formsmentioning
confidence: 99%
“…Gene models were created with two alternative methodologies using Nanopore direct RNA-seq long reads alone or in combination with our previously published Illumina short-read RNA-seq of mixed asexual and sexual blood stage parasites (Figure 2) (37). These parallel approaches are both informative, given the strengths and limitations of both sequencing techniques.…”
Section: Nanopore Direct Rna Sequencing Provides New Information To P...mentioning
confidence: 99%
“…The predicted genes were annotated using reciprocal BLAST against P. yoelii 17X proteins. Illumina RNA-seq reads were previously reported (37).…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it is reported that transcription factors of Apicomplexan Apetala 2 family (ApiAP2) member AP2-O3, also specifically active in the female gametocytes, is a transcription repressor that regulates the formation of female gamete ( Li et al., 2021 ). In addition, recently, Plasmodium yoelii negative on TATA-less1-G ( Py NOT1-G) was discovered to play dual and opposed sexual functions - reducing gametocyte commitment but supporting male (exflagellation) and female (preparing the female gamete for further development) gametogenesis ( Hart et al., 2021 ). Though Py NOT1-G is a key part of mRNA de-adenylation complex (Ccr4p-associated factor/carbon catabolite repression4/negative on TATA-less (CAF1/CCR4/NOT)) and plays a fundamental role in preserving the mRNAs that are critical to Plasmodium sexual and early mosquito stage development, the mRNAs is regulated by the complex during gametogenesis is yet to be found ( Hart et al., 2021 ).…”
Section: The Criticality Of Gametogenesis and Its Biologymentioning
confidence: 99%